(untitled) (Revista de História da UEG (REVHIST), 2021)
The present work briefly reflects on the historical construction of the representation of the Indian in Brazilian historiography and on the way in which this representation emerges in history textbooks focused on elementary education. The reflection is constructed based on the analysis of 7th grade books, published after the law 11,645 / 2008 and used by teachers in the teaching of history in the municipality of Marabá, state of Pará, emphasizing the issue of prejudice, racism and invisibility present both in written history and in manuals designed to provide historical knowledge. The analysis points to some advances, but also to the permanence of mistakes and stereotypes, characteristic of the historically constructed representation. In this sense, we try to think about the challenges and possibilities that teachers are currently facing to address the indigenous issue in the classroom. Keywords: Indians. Textbook. Historiography. Teaching Indigenous History.